Caracterização físico-química e efeito da galactomanana de sementes de Leucaena leucocephala (Lam.) De Wit no controle da obesidade - VIANA, Kátia Danielle Araújo Lourenço (2017)
Galactomannans are dietary fibers of the soluble type that can influence mechanisms that involve the control of appetite and consequent weight gain. Leucaena leucocephala (Lam.) de Wit is among the species of leguminous source of galactomannans. This study aimed to characterize Leucaena leucocephala galactomannan according to physical-chemical and structural parameters and evaluate its effect on the control of obesity in pre-clinical tests in rats. Galactomannan was obtained from manual withdrawal of the endosperm, dissolution in water, filtration and precipitation in ethanol. The yield of galactomannan was 8.8% and the water retention (7.08 g H2O/g polysaccharide) and oil (0.8 g oil/g polysaccharide) were similar to guar gum (Sigma®), used as an analytical standard. The scanning electron microscopy (SEM) revealed a polymer with an intense degree of surface porosity. The elements oxygen (54.9%), carbon (38.3%) and nitrogen (6.8%) dry matter composition according to the X-ray dispersive energy analysis (EDS). The monosaccharide composition presented mannose (59.44%) and galactose (39.60%) as major components and Man: Gal ratio of 1.5. Infrared spectroscopy (FTIR) analysis suggests a crystalline structure essentially formed by pyranoside rings of galactosyl residues and manipulations represented by vibratory stretches of functional groups such as C-O, C-C-O, C-OH, C-H and OH. The sample showed to be homogeneous with high molar mass and as rheological properties revealed that, in 5% aqueous solution, the galactomannan behaved with non-Newtonian and pseudoplastic fluid. To evaluate the effect of L. leucocephala galactomannan on obesity, 60-day-old female Wistar rats (Rattus norvegicus) received a hyperlipid diet for 18 weeks and were then randomly assigned to: GL group (n = 5), treated With 5% Gel of L. leucocephala galactomannan; GG (n = 5), treated with 5% guar gum gel (Sigma®) and COB group (n = 5), dropping distilled water (0.1 ml / 100 g). The non-obese control group (CNO, n = 5) received standard diet for rats (Nuvilab®). Treatments were performed daily by gavage for a period of 18 weeks. The variables analyzed were body mass, food and caloric intake, plasma levels of total cholesterol, HDL-c, triglycerides and fasting glycemia, hepatic markers (total cholesterol, triglycerides and total fat) and body fat (retroperitoneal, gonadal, visceral and abdominal adiposity). For the evaluation of gastric emptying and intestinal transit, 24 animals were divided into 4 groups (6 animals / group): control (CONT), atropine (ATP), guar gum (GG) and galactomannan of L. leucocephala (GL). Long-term treatment with the 5% galactomannan gel of L. leucocephala, compared to the control-obese group (COB), exerted a protective effect on the evolution of body weight (7.57% vs 11.5%) and reduced (7.63 g vs g), gonadal and visceral fat deposits (2.20% vs 3.54% and 1.20% vs 2.16%, respectively). The results indicate that the galactomannan of the seeds of L. leucocephala can be considered an important adjuvant in the use of galactomannans in biotechnological and industrial processes as well as in the therapy of obesity and its complications.